REPRESENTATION OF LOVE IN THE GODFATHER - Panggabean, Meicky Shoreamanis (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2023)
Research done in Italian prisons showed that the convicted mafia members exhibited significant antisocial traits but their capacity for emotional connection is higher than other imprisoned offenders in Italy. In another research, Schimmenti (2014) concluded that mafioso is more sensitive, family orientated, and less selfish than other murderers. In popular culture particularly in movies, mafioso is portrayed as callous and remorseless. Knowing that they can have emotional relationships, this study analyzes the types of love that are revealed in 'The Godfather', a mob movie that was nominated for 28 Oscars and won 9. The Ancient Greek has four different words for love: Agape, Eros, Philia, and Storge. This concept of love is popularized by CS Lewis and will be used as the basis of analysis. This research focused on the main character, Michael Corleone, and examined which type of love he expressed and to whom it poured out: His own family or his mafia family. The movie portrayed that Michael was only capable of loving his father and his daughter. He could express Storge yet was unable to have affection towards his wife (Eros) thus automatically did not have the capacity to love unconditionally (Agape).  He also had a hard time to have close relationship with anyone and did not love his brothers or sister, either (Philia).